IMPORTANCE OF THE MENTAL PREPARATION FOR COMPETITION AMONG YOUNG ATHLETES - Borók, Orsolya; Bácsné Bába, Éva (Stadium - Hungarian Journal of Sport Sciences, 2021)
The mental preparation of athletes for competition has become more appreciated. In this paper, we asked young athletes in Hungarian team sports about their experiences and expectations in mental preparation. In the research, we used an online questionnaire where 165 valuable responses were received. Most of the respondents were women, between 15-24 years of age, high school and college graduates, with urban background. Almost 90% of respondents have been confronted an obstacle with a negative impact on performance in sports before. Most athletes know well the activities of sports psychologists, however, only 10% of them have been mentally trained so far, while 70% of them would need it. Those sports associations achieve more successful results in the talent management, where sports psychologist was involved in the assessment of young children. Based on these, sports organizations should use a sports psychologist, because it could help achieve better sports performance for players and teams.